2021
DOI: 10.5546/aap.2021.eng.e353
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid-induced sinus bradycardia in a young boy with adrenal insufficiency and sepsis

Abstract: The literature does not commonly describe cardiac rhythm disturbances, including bradycardia, in patients who are receiving corticosteroids, and the exact mechanism of such disturbances remains unknown. Herein, we present a case of sinus bradycardia associated with stress-dose corticosteroid therapy. A nine-year-old boy with a history of panhypopituitarism was admitted with gastroenteritis and pneumonia and developed septic shock on the day of admission. Management using intravenous fluids, stress doses of hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…A literature review revealed that steroid-induced bradycardia is likely underdiagnosed because most patients are asymptomatic,2 7 8 in contrast to our case where the patient experienced symptoms. Although the bradycardia resolves spontaneously after discontinuation of the medication, it is also crucial to rule out other, more prevalent causes of bradycardia, such as hypothyroidism, electrolyte imbalance and the use of drugs including beta-blockers, calcium channel blockers and digitalis.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…A literature review revealed that steroid-induced bradycardia is likely underdiagnosed because most patients are asymptomatic,2 7 8 in contrast to our case where the patient experienced symptoms. Although the bradycardia resolves spontaneously after discontinuation of the medication, it is also crucial to rule out other, more prevalent causes of bradycardia, such as hypothyroidism, electrolyte imbalance and the use of drugs including beta-blockers, calcium channel blockers and digitalis.…”
Section: Discussioncontrasting
confidence: 68%
“…Total scores range from −4 to +13; a score of ≥9 is considered a definite adverse reaction, probable adverse reaction if 5–8, possible if 1–4 and doubtful if ≤0. In our case, the calculated score was 8, which suggests a probable adverse reaction 6 8 11…”
Section: Discussionmentioning
confidence: 63%